Clinical features and diagnosis of multiple myeloma: a population-based cohort study in primary care. Issue 10 (6th October 2021) - Seesaghur, Anouchka; Petruski-Ivleva, Natalia; Banks, Victoria Louise; Wang, Jocelyn Ruoyi; Abbasi, Ali; Neasham, David; Ramasamy, Karthik
Abstract : Objectives: Patients with multiple myeloma (MM) experience significant delays in diagnosis due to non-specific symptomatology. The aim of this study was to characterise the frequency and timing of clinical features in the primary care setting prior to MM diagnosis. Design: Population-based cohort study. Setting: Electronic health records data of approximately 17 million patients (2006–2016) within the UK Clinical Practice Research Datalink. Participants: Patients aged ≥18 years with newly diagnosed MM (NDMM), no history of solid tumours and ≥2 years registration in a primary care practice prior to MM diagnosis. Main outcome measures: Clinical features and symptoms including bone pain, skeletal-related events (SREs), investigation and confirmation of MM diagnostic CRAB criteria (hyperCalcaemia, Renal impairment, Anaemia, Bone lesions) during the 2 years prior to MM diagnosis; time between symptom manifestation and/or relevant investigation and diagnosis of MM. Results: Among 2646 patients with NDMM, 47.5% had a bone pain record during the 2-year period prior to MM diagnosis, mainly affecting the back. Regardless of baseline bone pain, investigations for serum calcium level were used in 36.4% of patients prior to MM diagnosis, followed by haemoglobin (65.6%) or renal function (74.1%). Median (Q1, Q3) time from first-recorded bone pain to MM diagnosis was 220 (80, 476) days. Median (Q1, Q3) time from first-recorded hypercalcaemia, renal impairment or anaemia to MM diagnosis was 23 (12, 46), 58 (17, 254) and 73 days (28, 232), respectively. An imaging investigation or referral for imaging was recorded for 60.0% of patients with bone pain/SRE and 32% without. Conclusions: Nearly half of patients diagnosed with NDMM presented with bone pain approximately 7 months prior to MM diagnosis. Investigations to evaluate all CRAB criteria, including targeted imaging, were underused. Early recognition of myeloma clinical features and optimised use of investigations in primary care may potentially expedite MM diagnosis.